The Antibiotic Immersion of Custom-Made Porous Hydroxyapatite Cranioplasty: A Multicentric Cohort Study. Issue 5 (14th July 2022) - Amendola, Francesco; Vaienti, Luca; Carbonaro, Riccardo; Nataloni, Angelo; Barbanera, Andrea; Zingaretti, Nicola; Pier, Camillo Parodi; Zanotti, Bruno
Abstract : Abstract: Cranioplasty is a common neurosurgical procedure performed to reconstruct cranial defects. The most common cranioplasty materials used today can be divided into 2 types: autologous bone and bone substitutes, such as polyetheretherketone, titanium mesh, poly-methyl methacrylate, and Hydroxyapatite (HA). Infection represents one of the most feared complications, ranging from 2.3% to 20%. Early implant infections occur within 30 days from the operation and are mostly due to pathogens from the skin and the paranasal cavity. The authors aim to demonstrate the efficacy of our preoperative antibiotic immersion protocol of custom-made HA prosthesis, to prevent early implant infections. The authors compare this population to cranioplasties without preoperative antibiotic elution and those with anonstandardized antibiotic elution. The authors retrospectively analyzed data from patients referred to 6 different hospitals in northern Italy, in the period 2000 to 2020. Inclusion criteria were patients requiring reconstruction of thecal bone with HA prosthesis after post-traumatic decompressive surgery; age more than 18 years; detailed patient history and clinical data; and follow-up of minimum 6 months. A total of 77 cranioplasties were included in the study, along with 120 retrospective cases in comparison. Infections occurred in 2.6% of cranioplasties with antibiotic immersion compared to 7.8% of cranioplasties without. Even if nonsignificant, these results support our hypothesis that pretreatment of HA implants with antibiotic appears to prevent cranioplasty infections and could be a viable option to improve cranioplasty outcomes in the future.